2002
DOI: 10.1111/j.1654-1103.2002.tb02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition of a Swedish semi‐natural grassland during six years of elevated atmospheric CO2

Abstract: Abstract. A semi‐natural grassland in Sweden was exposed to an elevated CO2 concentration during a six‐year open‐top chamber experiment. Vegetation composition was assessed twice a year using the point‐intercept method. The field had been grazed previously, but when the experiment started this was replaced with a cutting regime with one cut (down to ground level) each year in early August. From the third to the sixth year of the study the harvested material was divided into legumes, non‐leguminous forbs and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…During the drier year (2002) differences in composition were not as pronounced. Variation in compositional shifts under elevated [CO 2 ] caused by differential responses of species between years is not uncommon in community-level CO 2 -enrichment investigations (Vasseur & Potvin, 1998;Norton et al, 1999;Niklaus et al, 2001;Marissink & Hansson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…During the drier year (2002) differences in composition were not as pronounced. Variation in compositional shifts under elevated [CO 2 ] caused by differential responses of species between years is not uncommon in community-level CO 2 -enrichment investigations (Vasseur & Potvin, 1998;Norton et al, 1999;Niklaus et al, 2001;Marissink & Hansson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In studies focused on forest and grassland ecosystems from the same region and period, nitrogen deposition, sometimes in combination with soil acidification, has similarly been identified as the main driver of changes in the flora (Diekmann, Brunet, R€ uhling, & Falkengren-Grerup, 1999;Falkengren-Grerup, 1986, 1990Linusson et al, 1998). Similar, although less strong effects of eutrophication during the 1900s have been demonstrated further north in Sweden (Maad et al, 2009), as well as elsewhere in Europe and North America (Bobbink et al, 2010;von Numers & Korvenpaa, 2007;Walker et al, 2009 Furthermore, changes in land-use towards intensified agriculture and forestry have continued (Cousins et al, 2015), and new possible drivers of floristic changes such as increased atmospheric CO 2 levels (Marissink & Hansson, 2002;Sykes, 2007) and drastic declines in pollinating insects (Biesmeijer et al, 2006;Sorg, Schwan, Stenmans, & M€ uller, 2013; but see Carvalheiro et al, 2013) have been identified.…”
Section: Introductionmentioning
confidence: 91%
“…To summarize, recent and on-going changes in Scania and surrounding regions include (1) increasing forested area and numbers of trees in the landscape (Fredh et al, 2012), (2) decreasing numbers of grazing domestic animals and a smaller proportion of them being kept on low-productive semi-natural grasslands (Swedish Board of Agriculture, 2011), (3) rising temperatures (data from the Swedish Metrological and Hydrological Institute), (4) increasing atmospheric CO 2 levels (Marissink & Hansson, 2002) and (5) declining abundance of pollinating insects (Sorg et al, 2013). With the goal of being able to rank and evaluate the relative importance of these different potential drivers of floristic changes in the region, we present and analyse data from two readily comparable surveys (the Millora project).…”
Section: Introductionmentioning
confidence: 99%
“…Current projections forecast a doubling or tripling of preindustrial CO 2 concentrations by the end of the 21st century (IPCC, 2001). In the last two decades, an enormous body of research has demonstrated that elevated CO 2 , the primary substrate for photosynthesis, can have profound effects on plant growth and reproduction (Jablonski et al, 2002;Poorter & Navas, 2003), species interactions and community dynamics (Niklaus et al, 2001;Marissink & Hansson, 2002;Polley et al, 2003;Poorter & Navas, 2003), and ecosystem processes (Kö rner, 2000;Niklaus & Kö rner, 2004). Surprisingly little work has been done, however, on the potential consequences of rising CO 2 for plant evolution (see e.g.…”
Section: Introductionmentioning
confidence: 99%